Application of Public Relations Tools for Revenue Generation by Taraba State Board of Internal Revenue - Ubandoma, Rejoice; Ugondo, Peter Iorper (International Journal of Education, Management, and Technology, 2024)
This study investigates the efficacy of public relations (PR) tools employed by the Taraba State Board of Internal Revenue to bolster revenue generation. The research objectives encompass identifying specific PR strategies, eval_uating their effectiveness, and proposing actionable recommendations. Employing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted to gather comprehensive insights. The study was built on Two Symmetrical Model, Excellence Theory, and Transfer Process Model. Findings indicate a moderate utilization of PR tools, with 63% of respondents reporting extensive to moderate use. Notable strategies include social media engagement, press releases, and community outreach initiatives. Qualitative data elucidates participant experiences, highlighting the impact of these strategies on promoting tax compliance and fostering positive public perception. Effectiveness assessments reveal tangible outcomes, with participants citing increased tax compliance rates and positive media coverage as key indicators. This underscores the significance of strategic communication in driving revenue generation efforts. However, challenges such as limited collaboration with external stakeholders and the absence of comprehensive eval_uation mechanisms are identified. Based on the findings, several recommendations are proposed to optimize PR efforts and enhance revenue generation outcomes. These include fostering closer collaboration with stakeholders, implementing robust eval_uation mechanisms, and tailoring communication strategies to diverse audience segments. Additionally, there is a call for continuous professional development to ensure staff proficiency in PR roles.